Risk assessment of prospective investment projects for the construction of nuclear power plants abroad - I. Guseva, Anna; V. Koptelov, Matvey (International Journal of Engineering and Technology, 2018)
The article deals with the development of nuclear energy, classification of risks, approaches to risk assessment of investment projects of NPP construction abroad. Presented integrated methodology for assessing the risks of nuclear investment projects is based on the recommendations of the United Nations Industrial Development Organization (UNIDO), the International Atomic Energy Agency (IAEA), the sectoral methodological recommendations of the State corporation Rosatom. A way of accounting for risks in the calculation of economic efficiency is proposed. Calculations have been made for several real NPP construction projects (Rooppur NPP in Bangladesh, Astravets NPP in Belarus, Hanhikivi NPP in Finland). Analysis of the results of these projects shows that, taking into account all types of risks, its investment attractiveness has significantly decreased.Â